Discussion on the taxonomy of African fern Abrodictyum rigidum (Sw.) Ebihara & Dubuisson and description of two new Abrodictyum C.Presl species (Hymenophyllaceae, Polypodiidae) for the Afro-Malagasy region - Dubuisson, Jean-Yves; Bauret, Lucie; Grall, Aurelie; Li, Tian; Ebihara, Atsushi; Hennequin, Sabine (Phytotaxa, 2016)
The taxonomy of the genus Abrodictyum is complex, with many species showing similar gross morphology, especially those supposedly related to A. rigidum. Morphological and morphometric comparisons were performed on Neotropical A. rigidum specimens, African specimens first attributed to A. rigidum and two supposedly new distinct Abrodictyum species from the western Indian Ocean. All species share similar gross morphology and therefore are often confused in the wild and in herbarium collections. Morphological and morphometric analyses have not led us to the discrimination of distinct taxa or morpho-groups, except for one of the two supposedly new species, which appears to be endemic to Madagascar and shows some differences in frond shape, frond division and the indusium. Molecular analyses nevertheless confirm the distinctiveness of the Malagasy endemic new species, and the clustering of African A. rigidum with the second supposedly new species, both new taxa being consequently distinct from true Neotropical A. rigidum. We describe thus two new species: Abrodictyum pseudorigidum sp. nov., which is widespread in tropical Africa and in the western Indian Ocean and forms with true A. rigidum a pair of cryptic species, and Abrodictyum franceae sp. nov. endemic to Madagascar.